E-131 Optical coherence tomography-guided endovascular treatment of symptomatic non-stenotic carotid disease. (23rd July 2022) - Madhani, S; Oushy, S; Borg, N; Scharf, E; Savastano, L
Abstract : Introduction: Symptomatic non-stenotic carotid disease (SyNC) is an underrecognized etiology of cryptogenic ischemic stroke. Maximal medical therapy has limited efficacy against SyNC patients with certain plaque features. Endovascular treatment of SyNC in conjunction with multimodal imaging technologies is an unexplored frontier. We present a brief report of a case of SyNC that was endovascularly treated and guided by optical coherence tomography (OCT). Materials and Methods: A 74-year-old male with history of remote cryptogenic cerebellar stroke presented with self-limited episodes of dysarthria and left hemifield visual loss. Based on his clinical history and clinical examination, a diagnosis of stroke with cardioembolic or unstable atherosclerotic disease origin was made, and imaging was ordered accordingly. Results: Brain magnetic resonance (MR) imaging showed multifocal subacute and chronic right hemispheric infarcts. MR and CT angiography of the neck demonstrated <50% stenosis of the right ICA due to a partially calcified, possibly ulcerated plaque with intraplaque hemorrhage. Baseline OCT images demonstrated a large excavation within an ulcerated ICA plaque and thrombus. Patient was then treated with a carotid artery stenting under flow arrest. Post-stenting OCT confirmed the collapse of the intraplaque lumen by outward radial displacement of the fibrous cap and excellent stent wall apposition without atheroma protrusion. Conclusion: SyNC is increasingly being recognized as a potential etiology in cryptogenic ischemic strokes. Plaques can be evaluated through imaging modalities such as OCT providing insight towards targeted therapy for patients. Disclosures: S. Madhani: None. S. Oushy: None. N. Borg: None. E. Scharf: None. L. Savastano: None.